2016
DOI: 10.1007/s12185-016-2058-3
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of ribosomal genes is associated with a poor response to azacitidine in myelodysplasia and related neoplasms

Abstract: Azacitidine (AZA) is a hypomethylating drug used to treat disorders associated with myelodysplasia and related neoplasms. Approximately 50 % of patients do not respond to AZA and have very poor outcomes. There is thus great interest in identifying predictive biomarkers for AZA responsiveness. We searched for specific genes whose expression level was associated with response status. Using microarrays, we analyzed gene expression patterns in bone marrow CD34 cells in serial samples from 32 patients with myelodys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
2
12
1
Order By: Relevance
“…Wu et al showed RPL23 , a ribosomal gene was overexpressed in MDS CD34+ cells and associated with poor drug response 37 . Belickova et al also showed increased expression of multiple ribosomal genes correlates with poor azacitidine response and disease progression 38 . We further confirmed one of the top hits, RPL5 , showed significantly increased expression in the CD123+ compartment of the primitive compartment of a high-risk MDS patient in comparison to the CD123− compartment and the primitive compartment (Lin−/CD34+/CD38−) of normal bone marrow (Supplementary fig.…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al showed RPL23 , a ribosomal gene was overexpressed in MDS CD34+ cells and associated with poor drug response 37 . Belickova et al also showed increased expression of multiple ribosomal genes correlates with poor azacitidine response and disease progression 38 . We further confirmed one of the top hits, RPL5 , showed significantly increased expression in the CD123+ compartment of the primitive compartment of a high-risk MDS patient in comparison to the CD123− compartment and the primitive compartment (Lin−/CD34+/CD38−) of normal bone marrow (Supplementary fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another study of 200 CRC patients revealed a reduced OS associated with a higher level of RPS15A protein 24 . RPL28 upregulation was associated with reduced OS after azacytidine treatment in patients with myelodysplasia and related neoplasms 25 . These studies pointed toward potential functions of ribosome-free RPs that might engage an oncogenic role or suppressing tumor cell proliferation, depending on the RPs proteins involved 18 .…”
Section: Discussionmentioning
confidence: 94%
“…Data (NCBI GEO accession number GSE77750) from our previous genome-wide analysis performed using Illumina microarrays (HumanHT-12 v4 Expression, Illumina, San Diego, CA, USA) were used [ 30 ]. For this project, the expression of only five genes in the DLK1–DIO3 region ( DLK1, RTL1 , DIO3, MEG3, and MEG8 ) and of the CTCF was further considered within our patient cohort (the same 12 patients with MDS/AML-MRC) and 10 controls.…”
Section: Methodsmentioning
confidence: 99%